1996
DOI: 10.1111/j.1440-1681.1996.tb01189.x
|View full text |Cite
|
Sign up to set email alerts
|

POSSIBLE INVOLVEMENT OF MUSCARINIC M1 AND M3 RECEPTOR SUBTYPES MEDIATING VASODILATION IN ISOLATED, PERFUSED CANINE LINGUAL ARTERIES

Abstract: 1. Using the cannula insertion method, muscarinic receptor subtypes were analysed in isolated, perfused canine lingual arteries preconstricted with phenylephrine. 2. Both acetylcholine and McN-A-343 induced a profound vasodilation in a dose-related manner. Acetylcholine-induced dilations were approximately 1000-times more potent than McN-A-343-induced dilation. 3. Acetylcholine-induced dilations were abolished after removal of the endothelium by intraluminal treatment with 1 mg saponin. 4. Acetylcholine-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The odd-numbered muscarinic receptor subtypes (M 1 , M 3 , and M 5 ) have been reported to mediate endothelium-dependent vasodilation. Based on pharmacological studies making use of subtypepreferring agents, the M 1 receptor was suggested to be involved in cholinergic vasorelaxation of rat carotid arteries, the perforating branch of the human internal mammary artery, and human pulmonary and canine lingual arteries (10,29,32,36). Other classical pharmacological studies as well as functional studies in gene-targeted mice lacking specific muscarinic acetylcholine receptor subtypes demonstrated that the M 3 receptor mediates cholinergic vasodilation in various conduit vessels, such as the aorta and the femoral artery, and in some resistance vessels, such as coronary and ophthalmic arteries (2-3, 16, 20, 25).…”
mentioning
confidence: 99%
“…The odd-numbered muscarinic receptor subtypes (M 1 , M 3 , and M 5 ) have been reported to mediate endothelium-dependent vasodilation. Based on pharmacological studies making use of subtypepreferring agents, the M 1 receptor was suggested to be involved in cholinergic vasorelaxation of rat carotid arteries, the perforating branch of the human internal mammary artery, and human pulmonary and canine lingual arteries (10,29,32,36). Other classical pharmacological studies as well as functional studies in gene-targeted mice lacking specific muscarinic acetylcholine receptor subtypes demonstrated that the M 3 receptor mediates cholinergic vasodilation in various conduit vessels, such as the aorta and the femoral artery, and in some resistance vessels, such as coronary and ophthalmic arteries (2-3, 16, 20, 25).…”
mentioning
confidence: 99%
“…However, β‐adrenoceptor agonists caused only a small vasodilation, indicating the existence of a few β‐adrenoceptors in this artery. In 1996, Chiba and Tsukada 19 demonstrated that abundant functional M 3 and a few M 1 muscarinic acetylcholine receptors in the canine lingual artery, mediate marked vasodilation dependent on the presence of an intact endothelium. Chiba and Tsukada 20 also reported that histamine caused endothelium‐dependent vasodilation in this artery.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular responses to a number of vasoactive substances in the canine isolated lingual arteries have been reported previously 17 –20 . In dogs, the tongue assists in reducing body temperature and heat stress (heavy exercise or whole body warming) will readily induce a vasodilation in the canine tongue 21 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most vascular beds, stimulation of muscarinic receptors in the endothelium has been shown to release NO and produce muscle relaxation. However, there is controversy regarding which muscarinic receptor is involved in the release of NO in different vascular beds [4,6,14]. To clarify the muscarinic receptor subtype responsible for the increase in the NO release in rabbit renal arteries, effects of four different muscarinic subtype receptor antagonists were evaluated.…”
Section: Endothelial [Ca 2+mentioning
confidence: 99%